2011
DOI: 10.1038/bjc.2011.193
|View full text |Cite
|
Sign up to set email alerts
|

HOXC11–SRC-1 regulation of S100beta in cutaneous melanoma: new targets for the kinase inhibitor dasatinib

Abstract: Background:Cutaneous melanoma is an aggressive disease. S100beta is an established biomarker of disease progression; however, the mechanism of its regulation in melanoma is undefined.Methods:Expression of HOXC11 and SRC-1 was examined by immunohistochemistry and immunofluorescence. Molecular and cellular techniques were used to investigate regulation of S100beta, including, western blot, qPCR, ChIP and migration assays.Results:Expression levels of the transcription factor HOXC11 and its coactivator SRC-1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…These results clearly identified CSF1 as a direct novel target gene of NCOA1 and c-Jun/c-Fos in BrCa cells. Recent studies have also demonstrated that NCOA1 serves as a coactivator for PEA3, c-Jun/c-Fos, Ets-2 and HOXC11 to upregulate Twist1 , integrin α 5 ( ITGA5 ), c-Myc and S100β expression, respectively, which in turn promotes BrCa cell EMT, migration, invasion and/or resistance to endocrine therapies (18, 19, 46, 47). Together, these findings indicate that NCOA1 can coactivate different TFs to regulate multiple target genes important for BrCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly identified CSF1 as a direct novel target gene of NCOA1 and c-Jun/c-Fos in BrCa cells. Recent studies have also demonstrated that NCOA1 serves as a coactivator for PEA3, c-Jun/c-Fos, Ets-2 and HOXC11 to upregulate Twist1 , integrin α 5 ( ITGA5 ), c-Myc and S100β expression, respectively, which in turn promotes BrCa cell EMT, migration, invasion and/or resistance to endocrine therapies (18, 19, 46, 47). Together, these findings indicate that NCOA1 can coactivate different TFs to regulate multiple target genes important for BrCa.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting NCOA1 could inhibit CSF1 expression and CSF1 expression-induced BrCa cell invasion and metastasis. Given that NCOA1 also upregulates other genes important for BrCa cell survival, invasion and metastasis, such as Twist1 , ITGA5 , c-Myc and S100β (18, 19, 46, 47), NCOA1 may be a potential molecular target for inhibiting BrCa progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment with the Src/Abl inhibitor, dasatinib, reduced the HOXC11-SRC-1 interaction and prevented recruitment of HOXC11 to the S100B promoter, so the mRNA and protein levels for S100B were both reduced, as was the growth and migratory properties of drug-treated MeWo melanoma cells. Thus, profiling patients for HOXC11 and S100B levels has the potential to increase the efficacy of dasatinib treatment in melanoma [415]. It is also noteworthy that the effect of specific drugs can be tissue-specific, particularly for regulation of the S100A2 gene, which is thought to suppress growth in some cell types (i.e.…”
Section: Therapeutic Considerations For the S100 Protein Familymentioning
confidence: 99%
“…Dasatinib treatment also inhibited migration of SK-MEL-28 cells via decreased phosphorylation of FAK [135]. Migration of metastatic melanoma cells harvested from lymph nodes (MeWo cells) was decreased by dasatinib-mediated inhibition of homeobox C11 (HOXC11) protein interactions with Src [136]. Dasatinib treatment of uveal melanoma cells injected into zebrafish models has also demonstrated potent anti-migratory effects [137].…”
Section: Effects Of Small Molecule Inhibitors On Emt In Melanomamentioning
confidence: 99%